Susceptibility and Severity of COVID-19 Are Both Associated With Lower Overall Viral–Peptide Binding Repertoire of HLA Class I Molecules, Especially in Younger People - Basir, Hamid Reza Ghasemi; Majzoobi, Mohammad Mahdi; Ebrahimi, Samaneh; Noroozbeygi, Mina; Hashemi, Seyed Hamid; Keramat, Fariba; Mamani, Mojgan; Eini, Peyman; Alizadeh, Saeed; Solgi, Ghasem; Di, Da (Frontiers in Immunology, 2022)
An important number of studies have been conducted on potential association between Human Leukocyte Antigen (HLA) genes and COVID-19 susceptibility and severity since the beginning of the pandemic. However, case-control and peptide-binding prediction methods tended to provide inconsistent conclusions on risk and protective HLA alleles, whereas some researchers suggested the importance of considering the overall capacity of an individual’s HLA Class I molecules to present SARS-CoV-2-derived peptides. To close the gap between these approaches, we explored the distributions of HLA-A, -B, -C and -DRB1 (1st-filed) alleles in 142 Iranian COVID-19 patients and 143 ethnically matched healthy controls, and applied in silico predictions of bound viral peptides for each individual’s HLA molecules. Frequency comparison revealed possible predisposing roles HLA-A*03, B*35 and DRB1*16 alleles and protective effect of HLA-A*32, B*58, B*55 and DRB1*14 alleles in the viral infection. None of these alleles remained significant after multiple testing corrections, except HLA-A*03, and none was associated to severity, either. Compared to peptide repertoires of individual HLA molecules which are more likely population-specific, the overall coverage of virus-derived peptides by one’s HLA Class I molecules seemed to be a more prominent factor associated to both COVID-19 susceptibility and severity, which was independent of affinity index and threshold chosen, especially for people under 60 years old. Our results highlight the effect of the binding capacity of different HLA Class I molecules as a whole, and the more essential role of HLA-A compared to HLA-B and -C genes in immune responses against SARS-CoV-2 infection.